What do editors do? Understanding the physiological functions of A-to-I RNA editing by adenosine deaminase acting on RNAs - Heraud-Farlow, Jacki E. (Open Biol, 2020)
Adenosine-to-inosine (A-to-I) editing is a post-transcriptional modification of RNA which changes its sequence, coding potential and secondary structure. Catalysed by the adenosine deaminase acting on RNA (ADAR) proteins, ADAR1 and ADAR2, A-to-I editing occurs at approximately 50 000–150 000 sites in mice and into the millions of sites in humans. The vast majority of A-to-I editing occurs in repetitive elements, accounting for the discrepancy in total numbers of sites between species. The species-conserved primary role of editing by ADAR1 in mammals is to suppress innate immune activation by unedited cell-derived endogenous RNA. In the absence of editing, inverted paired sequences, such as Alu elements, are thought to form stable double-stranded RNA (dsRNA) structures which trigger activation of dsRNA sensors, such as MDA5. A small subset of editing sites are within coding sequences and are evolutionarily conserved across metazoans. Editing by ADAR2 has been demonstrated to be physiologically important for recoding of neurotransmitter receptors in the brain. Furthermore, changes in RNA editing are associated with various pathological states, from the severe autoimmune disease Aicardi-Goutières syndrome, to various neurodevelopmental and psychiatric conditions and cancer. However, does detection of an editing site imply functional importance? Genetic studies in humans and genetically modified mouse models together with evolutionary genomics have begun to clarify the roles of A-to-I editing in vivo. Furthermore, recent developments suggest there may be the potential for distinct functions of editing during pathological conditions such as cancer.